Bioactive compounds of rice bran and their potential health benefits in the development of functional foods: A review - Miftahurrahmi Miftahurrahmi; Teti Estiasih; Siti Narsito Wulan (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Rice bran is a by-product produced from the milling and polishing process of rice, which makes up about 10% of the whole grain. In 2021, the amount of rice bran produced in Indonesia can reach up to 3 million tons. Researchers have been intrigued to study rice bran as an ingredient for foods because it is considered underutilized despite its abundance and functional properties. Rice bran is rich in nutrients such as fat, protein, dietary fiber, ash, and bioactive compounds. There is an increase in the use of rice bran following consumers’ search for healthier consumption. Bioactive compounds in rice bran include phenolic acids, such as ferulic acid; flavonoids and anthocyanins, such as cyanidin glucoside; steroidal compounds, such as gamma-oryzanol; gamma-aminobutyric acid (GABA); etc. Rice bran’s wax contains wax esters and aliphatic alcohols, namely policosanol. Bioactive compounds in rice bran have been known to have beneficial effects on health as antioxidants, antidiabetic, and anti-inflammatory agents. The bioactive compounds of rice bran as well as its antioxidant activity are influenced by rice variety, degree of milling, and processing method. This paper aims to review the bioactive compounds of rice bran, including pigmented rice bran, to support the development of functional foods.